CONFUCIANISM THOUGHTS ON EDUCATION IN VIETNAM AND ITS EFFECT ON THE EDUCATION OF VIETNAM TODAY - Hong Vu, Van (2022)
Confucianism is a socio-political doctrine originating in China, born about 2.600 years ago. One of the unique contents of this theory is the idea of ​​education. Confucianism scriptures show that Confucianism thought on education holds an important position in the entire content of Confucianism. The influence of Confucianism, including thoughts on education, affect Vietnam very early and was received by the feudal dynasties of Vietnam. Historically, Confucian thought on education was used by the feudal dynasties of Vietnam to govern the country as well as train mandarins to serve the court policy. Studying Vietnam's ancient documents will reveal the important place Confucianism in education has played in history and realize how that thought was used by Vietnam's feudal dynasties. If negative factors are removed, Confucian thought on education has certain historical value as well as its value to Vietnam's education in the current period.